2017
DOI: 10.2208/kaigan.73.i_589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Computational Parameters on Accuracy of Movable Bed Model for Tsunamis

Abstract: 2 関西電力株式会社 土木建築室 技術グループ(〒530-8270 大阪市北区中之島3-6-16) 3 関西電力株式会社 土木建築室 土木建築エンジニアリングセンター (〒553-0003 大阪市福島区福島5-1-7 住友不動産西梅田ビル4F) 4 株式会社ニュージェック 港湾・海岸グループ(〒530-8270 大阪市北区本庄東2-3-20) 5 正会員 株式会社ハイドロソフト技術研究所(〒530-6126 大阪市北区中之島3-3-23 中之島ダイビル26F) 6 株式会社ハイドロソフト技術研究所(〒530-6126 大阪市北区中之島3-3-23 中之島ダイビル26F) 7 ふじのくに地球環境史ミュージアム(〒422-8017 静岡市駿河区大谷5762) 本研究では,津波移動床モデルにおける飽和浮遊砂濃度および流砂量係数の設定が地形変化の再現性に及 ぼす影響を把握するために,東北地方太平洋沖地震津波による岩手県高田海岸における地形変化の再現計 算を行った.その結果,得られる砂移動量の計算値が飽和浮遊砂濃度の設定方法によって大きく異なるこ とが明らかとなった.飽和浮遊砂濃度を固定値として与えると,十分な巻き上げが許容… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The STM considers sediment exchange between the bed and suspended loads assuming a single grain-size class of the sediments. Previous studies have extensively utilized TUNAMI-STM and its derivatives to investigate tsunami-induced sediment transport due to the 2011 Tohoku-oki earthquake (Sugawara et al 2014b;Yamashita et al 2016Yamashita et al , 2018Arimitsu et al 2017;Kusumoto et al 2020) and to model the paleotsunami source of the 1867 Keelung earthquake (Sugawara et al 2019). Sugawara et al (2014b) demonstrated that the general trend of deposit thickness along orthogonal transects to the shoreline can be reproduced using STM.…”
Section: Numerical Model and Inputsmentioning
confidence: 99%
“…The STM considers sediment exchange between the bed and suspended loads assuming a single grain-size class of the sediments. Previous studies have extensively utilized TUNAMI-STM and its derivatives to investigate tsunami-induced sediment transport due to the 2011 Tohoku-oki earthquake (Sugawara et al 2014b;Yamashita et al 2016Yamashita et al , 2018Arimitsu et al 2017;Kusumoto et al 2020) and to model the paleotsunami source of the 1867 Keelung earthquake (Sugawara et al 2019). Sugawara et al (2014b) demonstrated that the general trend of deposit thickness along orthogonal transects to the shoreline can be reproduced using STM.…”
Section: Numerical Model and Inputsmentioning
confidence: 99%
“…Numerical simulations using wave dynamics of an area can reproduce spatial-temporal variations in the sediment mobility and deposition and can effectively model the sediment transport process using the wave and sediment characteristics of the natural system. In recent years, numerical modeling of tsunami sediment transport has been developed (e.g., Takahashi et al, 2000), improved (e.g., Takahashi et al, 2011;Apotsos et al, 2011a;Li and Huang, 2013;Morishita and Takahashi, 2014;Yamashita et al, 2018) and applied in the field (e.g., Gelfenbaun et al, 2007;Takahashi et al, 2008;Apotsos et al, 2011b, c;Gusman et al, 2012;Li et al, 2014;Arimitsu et al, 2017;Yamashita et al, 2017), and reproducibility has been confirmed by comparison between the calculated and measured values (e.g., Li et al, 2012;Ranasinghe et al, 2013;Sugawara et al, 2014a;Yamashita et al, 2015;Yamashita et al, 2016).…”
Section: Introductionmentioning
confidence: 96%